Pengaruh Pembelajaran Blanded Learning terhadap Hasil Belajar Kelas X IPS Seni Rupa SMA Pertiwi 1 Padang - Harahap, Maulida Eka Wahyu; Wikarya, Yusron (TSAQOFAH, 2023)
The purpose of this study was to determine the effect of Blended Learning on learning outcomes for class X IPS in learning two-dimensional art at SMA Pertiwi 1 Padang. This study uses a quantitative method with a true experimental type. The research population is class X IPS. The research sample used a random sampling technique. Research instruments in the form of tests and observations. The data analysis technique used the t-test technique by utilizing the SPSS 16 program. The findings in this study were that class X IPS 1 students were classified as good using blended learning compared to classes X IPS 2 and 3. The results of this study indicated that there was a significant effect of learning Blended Learning on the learning outcomes of class X IPS students in learning two-dimensional art at SMA Pertiwi 1 Padang. This can be seen from the completeness of the learning outcomes of students who use blended learning, the experimental class which completes as many as 35 students (100%), not complete (0%). Whereas in the control class with conventional learning, the completeness of student learning outcomes was only 24 students (65%), 13 students (35%) did not complete.